2018
DOI: 10.2106/jbjs.oa.17.00043
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rotator Cuff Repair on Natural History

Abstract: Background:Rotator cuff disease can have a progressive natural history of increasing tear size and worsening function. It remains unknown whether rotator cuff repair alters this natural history.Methods:A systematic review of the intermediate to long-term (minimum 5-year) results of operative rotator cuff repair and no repair of rotator cuff injuries was performed to compare (1) patient-based outcomes, (2) future surgical intervention, (3) future tear progression or recurrence, and (4) tear size. The no-repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…However, the current literature does not seem to indicate clearly any signi cant clinical difference in terms of improvement of pain and functional disability between the two types of care (13). A recent systematic review showed that outcomes were similar for both treatment approaches (14). However, all these reviewed studies, except two randomized controlled clinical trials, were cohort studies without external control groups, and the studies consisting of conservatively treated patients generally included patients with small or medium sized tears, whereas the surgically treated patients typically presented with large or massive tears.…”
Section: Introductionmentioning
confidence: 88%
“…However, the current literature does not seem to indicate clearly any signi cant clinical difference in terms of improvement of pain and functional disability between the two types of care (13). A recent systematic review showed that outcomes were similar for both treatment approaches (14). However, all these reviewed studies, except two randomized controlled clinical trials, were cohort studies without external control groups, and the studies consisting of conservatively treated patients generally included patients with small or medium sized tears, whereas the surgically treated patients typically presented with large or massive tears.…”
Section: Introductionmentioning
confidence: 88%
“…The mean Constant score in those with arthropathy was 47, and mean 65 in those with full-thickness tear without arthropathy. A recent review by Chalmers et al from 2018 found a total of 289 patients with mid to longterm results for unrepaired rotator cuff tears (including those from paper I) and the mean duration of follow-up was 14.9 years (95% CI, 11.5-18.3 years) 39 . Paper I therefore seems to have the longest follow-up of unrepaired tears published until now.…”
Section: Acromioplasty Without Cuff Repairmentioning
confidence: 99%
“…Paper I therefore seems to have the longest follow-up of unrepaired tears published until now. In this review, 1 294 patients from 23 studies with outcome after repair were compared to 289 patients with unrepaired tears from 8 studies 39 . The repair group had a larger tear size at inclusion and the duration of follow-up was longer in the unrepaired group.…”
Section: Acromioplasty Without Cuff Repairmentioning
confidence: 99%
“…R otator cuff repair remains an imperfect treatment for a rotator cuff tear, with retears remaining a common issue, especially with large tears. [1][2][3][4][5] To combat this issue, there has been a great deal of research into the repair technique, with much of this effort focused on the placement pattern and number of suture anchors relative to the tendon footprint. 2,4 Specifically, much of this debate has focused on whether 2 rows of anchors provide sufficiently better outcomes or better tendon healing to justify their increased cost and surgical time.…”
Section: See Related Article On Page 2803mentioning
confidence: 99%
“…These results suggest that footprint coverage may be less important than previously thought regarding restoration of a full tendon attachment. Anatomic restoration is likely going to be important if our goal is for repair to interrupt the natural history of rotator cuff tears, 3 which is not benign. 24,25 Yamakado 20 has focused this study on medium-sized tears, which typically have high healing rates.…”
Section: See Related Article On Page 2803mentioning
confidence: 99%